Improving Mathematics Problem-Solving Ability With Problem-Based Learning in V Grade Students - Saputra, Hardika (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Nowadays, the ability of students in solving problems is very important. The teacher as a facilitator must present learning that is interesting and easy to understand. One alternative that can be done is to apply a problem-based learning model. This study aims to determine whether there is a significant improvement in the mathematical problem-solving ability of fifth-grade students of Aisyiyah Metro Elementary School after problem-based learning is applied. This research was conducted using a quantitative research method with the type of experimental research and using a quasi-experimental design in the form of a non-equivalent control group design. The sample in this study was the fifth-grade students of Aisyiyah Metro Elementary School with a total of 37 students divided into 2 classes, namely the experimental and the control class. Data collection techniques in this study used three methods, namely: observation, problem-solving ability tests, and documentation. The results of the study concluded that there was a significant increase in mathematical problem-solving ability in classes using problem-based learning compared to classes using conventional learning.